Characterization Of Cambodian Clays And Their Suitability For Ceramic Tiles Applications - Bun , Kim Ngun (2012)
The present work is aimed to provide detail scientific data on characterization of Cambodian clays and their suitability for ceramic tiles applications. The study covered three parts – Part I deals with characterization of the properties of the raw clay samples, Part II deals with investigation on changes of the properties between bulk and clay fraction (< 2 μm), and Part III deals with optimization of ceramic tile compositions incorporating Cambodian clays by using statistical design technique.